Encontro marcado com a crônica no romance de Fernando Sabino - Costa, Suzana Barbosa (2007)
The present dissertation has the main object to study the book O Encontro Marcado wrote by Fernando Sabino. This dissertation has pursuance to apprehend the concept of hybridization between chronicle and romance. To achieve this point of view it researches this question: How to developer the transition between i-storyteller, already this writer introduces two roles: he narrates and makes this an experience of his existence? Trying to responder this questionable, he selects hypothesis: the transient between I-subject and I-another one to determine and configure the cronicles s discourse and to manifest the experimental modern narrative contaminate by journalistic media. The I who describe and the I lively putted on proof to commit the role s character within the cronicle s discourse. The theory s grounding that to direct this works is the Bakhtin s theory, already this romance construe further on the studies about chronicle approached by Antonio Candido and Jorge de Sá. This works stand up for Fernando Sabino s critical fortune personated by Antonio Candido, Fábio Lucas and Antonio Houaiss. This dissertation was divided in three chapters. The first one focus on writer s trajectory and analyze the book. The second one approach the concept s hybrid and chronicle trying realize the question about fictional and autobiography s discourse. The last one approach the trajectory s Eduardo Marciano and his friends. The main conclusion is the analysis if the writer transferred to book the chronicle gender s characteristics, what experiences makes the writer object of experiences lively and writer s failure of his generation